Myoglobinuria: the importance of reaching a firm diagnosis–a patient with defective fatty acid oxidation. Issue 773 (March 1990) - Ellis, C. J.; Dewhurst, A. G.; Cooper, M.; Brenton, D. P.; Dathan, J. R.
Abstract : A 52 year old man presented with myoglobinuria-induced acute renal failure requiring dialysis. Despite renal biopsy, the cause of the myoglobinuria was not established until he re-presented a year later with a milder episode. At this stage investigations, including a muscle biopsy, demonstrated a defect in fatty acid oxidation amenable to dietary and lifestyle advice. This report emphasizes the importance of reaching a definitive diagnosis in myoglobinuria.